Analyze Factors That Affect Carbon Emission Disclosure (Case Study in Non-Financial Firms Listed on Indonesia Stock Exchange in 2014-2016) - Hapsari, Cantika Anindya; Prasetyo, Andrian Budi (Universitas Negeri Semarang, 2020)
The objective of this study is to find out what factors that can have an impact on carbon emissions disclosure in non-financial companies listed on the Indonesia Stock Exchange that publish sustainability reports for the year 2014-2016. The variables that would be tested in this study are independent variables consisting of industry type, company size, profitability, leverage and corporate governance, as well as the dependent variable which is the carbon emissions disclosure. Based on secondary data and purposive sampling methods, a total of 57 companies were obtained as research samples. Multiple linear regression is used as a model analysis of this study. Based on the test results, it has been found that the variables that have a significant influence on the level of carbon emissions disclosure are industry type, company size and leverage, while the remaining variables were found to have no significant effect.